How old is the Hebrew bible?: a linguistic, textual, and historical study - Hendel, Ronald S. (The Anchor Yale Bible Reference Library, 2018)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Preface, or, Why Did We Write This Book? -- List of Abbreviations -- 1. All Things Change: Language and Method -- 2. Kinds and Causes of Linguistic Change -- 3. How to Handle Linguistic Variation -- 4. Textual History and Linguistic History -- 5. Inscriptions and Preexilic Hebrew Literature -- 6. Transitional Biblical Hebrew -- 7. Pseudoclassicism: Late Biblical Hebrew and Qumran Hebrew -- 8. Consilience and Cultural History: The Ages of Biblical Literature -- Appendix 1. Historical Linguistics and the Books of the Hebrew Bible: A Bibliographical Survey -- Appendix 2. A Critique of the Revisionist Model -- Notes -- Bibliography -- Index of Scripture and Other Ancient Sources -- Index of Authors -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z -- Index of Subjects -- A -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- W -- Y -- Index of Words and Expressions